2019
DOI: 10.1038/s41419-019-1364-0
|View full text |Cite
|
Sign up to set email alerts
|

A30P mutant α-synuclein impairs autophagic flux by inactivating JNK signaling to enhance ZKSCAN3 activity in midbrain dopaminergic neurons

Abstract: Mutations in α-synuclein gene have been linked to familial early-onset Parkinson’s disease (PD) with Lewy body pathology. A30P mutant α-synuclein is believed to suppress autophagic progression associated with PD pathogenesis. However, the mechanistic link between A30P mutation and autophagy inhibition in PD remains poorly understood. In this study, we identified that A30P mutant α-synuclein resulted in reduced autophagy flux through promoting the decrease of autophagosomal membrane-associated protein LC3 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…Although several a-syn PDassociated mutants have been shown to promote a-syn oligomerization and/or fibril formation in vitro (de Oliveira & Silva, 2019;Ruf et al, 2019), in cells (M. B. Fares et al, 2014;Khalaf et al, 2014;Lei, et al, 2019) and in vivo (Mbefo et al, 2015;Paumier et al, 2013), Lázaro et al reported identical Venus BiFC signals from WT a-syn and the PD-linked mutants A30P, E46K, H50Q, G51D and A53T (Lázaro et al, 2014). Similar observation were made by Outeiro et al using a GFP-BiFC cellular assay (Outeiro et al, 2008).…”
Section: Discussionsupporting
confidence: 58%
“…Although several a-syn PDassociated mutants have been shown to promote a-syn oligomerization and/or fibril formation in vitro (de Oliveira & Silva, 2019;Ruf et al, 2019), in cells (M. B. Fares et al, 2014;Khalaf et al, 2014;Lei, et al, 2019) and in vivo (Mbefo et al, 2015;Paumier et al, 2013), Lázaro et al reported identical Venus BiFC signals from WT a-syn and the PD-linked mutants A30P, E46K, H50Q, G51D and A53T (Lázaro et al, 2014). Similar observation were made by Outeiro et al using a GFP-BiFC cellular assay (Outeiro et al, 2008).…”
Section: Discussionsupporting
confidence: 58%
“…In primary VM neurons transfected with A30P aSyn AAV vectors, aggregated p62 increased in a manner similar to that of the E46K mutant aSyn (Yan et al, 2014;Lei et al, 2019). A30P did not alter p62 mRNA levels, and 3-MA treatment increased p62 in both the mutant and empty AAV vector cells, supporting the conclusion that the insoluble aggregates were due to A30P-mediated autophagy inhibition (Lei et al, 2019). Like E46K, A30P also reduced LC3-II synthesis (but not degradation), suggesting a similar mechanism of impaired autophagosome formation (Yan et al, 2014;Lei et al, 2019).…”
Section: A30pmentioning
confidence: 82%
“…During the symptomatic stage of PD, when most dopaminergic neurons in the midbrain are already lost, the TFEB-mediated transcription of Beclin-1, CTSD, and LAMP1 is decreased compared to the pre-symptomatic stage [151]. Moreover, the expression of human A30P α-synuclein increased the nuclear translocation of the transcriptional repressor zinc finger protein with KRAB and SCAN domains 3 (ZKSCAN3), which regulates the transcription of LC3 and p62 [152]. As expected, the pathological features of PD, including neurodegeneration in the midbrain, motor dysfunction, and α-synuclein accumulation, were improved by TFEB overexpression [153,154].…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%